Differential proteomic of plasma provides a new perspective on scientific diagnosis and drug screening for dampness heat diarrhea in calves - Yan, Zunxiang; Zhang, Kang; Wang, Guibo; Wang, Lei; Zhang, Jingyan; Qiu, Zhengying; Guo, Zhiting; Zhang, Kai; Li, Jianxi (Frontiers in Veterinary Science, 2022)
Dampness heat diarrhea (DHD) is one of the most common syndromes of calf diarrhea. Its complexed etiology and lack of objective diagnostic criteria bring great challenges to the diagnosis and treatment of this disease. The aim of this study is to screen some prospective diagnostic biomarkers or therapeutic targets for calves DHD through investigating the differential protein profiles of plasma between DHD calves and clinically healthy calves by mass spectrometry based proteomic. A total of 120 DHD calves and 90 clinically healthy calves were divided into two groups randomly, 30 DHD calves and 30 clinically healthy calves in test group, and 90 DHD calves and 60 clinically healthy calves in validation group. In test group, a total of 52 proteins were differentially expressed between calves with DHD and clinically healthy calves, and 13 proteins were significantly increased and 39 proteins were significantly decreased. The differentially expressed proteins were associated with the intestinal immune network of IgA production, and caffeine metabolism, purine metabolism, PI3K signaling pathway. In validation group, 13 proteins were selected from 52 differential expression proteins for parallel reaction monitoring validation to verify their associations with DHD calves. The targeted proteomic results showed that fibronectin precursor (FN1) and apolipoprotein C-IV precursor (APOC4) were significantly associated with DHD in calves, and they were down-regulated in sick calves. In conclusion, the differential expression of plasma proteins were associated with DHD pathogenesis in calves, and the FN1 and APOC4 might be the potential clinical biomarkers for diagnosis of DHD in calves, and the intestinal immune network of IgA production, caffeine metabolism, purine metabolism and PI3K signaling pathway are the candidate targets to treat DHD in calves. Our finding provides a reference for further investigating the pathogenesis, developing techniques of diagnosis and screening treatment drugs for DHD in calves.